Climate change and hunger: Africa's smallholder farmers struggle to adapt - Ringler, Claudia (Wiley, 2010)
Climate Change and Hunger: Africa’s Smallholder Farmers Struggle to AdaptFarmers in Sub‐Saharan Africa are already feeling the effects of climate change, but many have done little or nothing in response. Researchers from the International Food Policy Research Institute (IFPRI) and their partners studied the perceptions of climate change among smallholder farmers in Ethiopia, Kenya and South Africa. They found that a lack of access to credit, markets, information, risk‐sharing tools, and property rights has limited the ability of many farm households to adapt to the negative effects of climate change. This article discusses on‐the‐ground findings in the context of computer model projections that show a decline in future yields of staple crops under most climate change scenarios. It concludes that adaptation to rising temperatures and changing weather patterns is crucial to the food security of millions of people. Without significant investment in agricultural technology and rural development, however, many farmers in Sub‐Saharan Africa will be unable to meet the challenges of the coming decades. As a result, calorie availability would drop dramatically and millions more children will be malnourished in 2050. Some of this funding could be secured if agricultural mitigation activities, which have important synergies with adaptation in the region, could be included in global carbon markets. But the political will and resources to support ‘charismatic carbon’– that is, lower entry barriers for pro‐poor adaptation and mitigation – have yet to be realised.